Dialectal Meanings in the Livestock Farming Lexicon of the Region of Casanare, Colombia - Vaca Vega, María Isabel; Rivera Salcedo, Delfín (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article is part of the research project Dialectal Lexicon from Livestock Farming Community in Casanare, Colombia. This project seeks to characterize this speech community and identify some of its usual linguistic phenomena, autochthonous vocabulary and sociological impact in this area. The research was a descriptive-explanatory dialectal study with a quantitative-qualitative tendency, which theoretically and empirically describes the the use of certain dialectal expressions. Through this analysis, it was found that, dialectal terms in livestock farming community from Casanare (Colombia) have become a rhetorical resource with a pragmatic role: enabling an easier and more fluid contact between conversational partners. In the same way, we found that linguistic variations, synonymy and polysemy are usual characteristics of most of the lexical samples studied, which present different alternatives to refer to the same things.